Development Of A Computer-Controlled Automated Storage And Retrieval System - Jantan, Sa'diah (2008)
Industrial demands for higher productivity require the replacement of the traditional control equipment with newer solutions that take advantage of the latest technologies. Programmable Logic Controllers (PLCs) based system has been the main choice for control equipments for the last decades. With the rapid advancement of computing technologies, the importance of PC-based system increased remarkably in the last few years. Retrofitting the PLC based system with the PC-based system offers many advantages. Among these advantages are PC-based systems are more flexible, easy integration, lower costs, better human machine interface (HMI) facilities. The implementation of a PC based motion control on a three-axis ASRS system is the main focus of this work. The scope of the work covers the implementation of two hardware platforms for the proposed system and to implement PID system on the two platforms. The development of GUI for the ASRS system provides the users with a comprehensive and user friendly interface to control the system. The performances of two types of hardware platforms; PCI 7344 motion controller card and (FP) 2000 Field point is compared based on trapezoidal motion profile. Both platforms are controlled by a proportional-integral-derivative (PID) controller. The parameters for the controller are determined experimentally. The experimental results show that both platforms successfully tracked the motion profile, and the tracking performance improves as the velocity of the system increase. Overall this work shows that PC-based system offers many advantageous to control and ASRS system.